Algorithmic Conversion of Data Displayed on a Weekly Basis to the Monthly Level Using the Spreadsheet. (2016) - Martinović, Marko; Stoić, Marija; Duspara, Miroslav; Samardžić, Ivan; Stoić, Antun
Abstract: This paper presents an algorithmic conversion process of data written on a weekly basis in the format of data on a monthly basis, including all the data specifics. The aim is to graphically and numerically display the results of the conversion and the size of the errors that is the time running. The main method used for averaging data is average data value. Research shows that the conversion error, ie. loss of the original value is below 2.5%.